Effect of Fenugreek (Methi) on Amount of Connective Tissue in Thymic Sections in Streptozotocin-induced Diabetic Rats (Bangladesh Journal of Anatomy, 2011)
Context: Diabetes mellitus causes a marked increased in amount of connective tissue in thymus. Fenugreek has the hypoglycaemic effect. The study was carried out to find out whether Trigonella foenumgraecum (fenugreek seeds/methi seeds) has got any preventive role against the increment in amount of connective tissue in thymic section in diabetes mellitus. Study type: an experimental study on Long Evans rats which were divided into three equal groups depending on their different sorts of dietary feeding and drug treatment. Setting: Anatomy department of the then IPGMR (Institute of Post Graduate Medicine and Research) at present BSMMU (Bangabandhu Sheikh Mujib Medical University) and BIRDEM (Bangladesh Institute of Research and Rehabilitation in diabetes, Endocrine & Metabolic Disorders). Subjects: Fifty eight healthy young Long Evans rats of either sex weighing 72 to 174gm aged between 50 to 60 days were used in this study. Main outcome measures: variation in amount of connective tissue in thymic sections in different groups of rats. Result: in the nondiabetic control group the increased in amount of connective tissue in thymic section is lower than in diabetic control group. On the other hand, the increased in amount of connective tissue in thymic section in the fenugreek-treated diabetic rats is also lower than the amount of connective tissue in thymic section in diabetic control group but it is more or less similar to the amount of connective tissue in thymic section in nondiabetic control group. Conclusion: Fenugreek showed a tendency of acting against the increased in amount of connective tissue in thymic section in Streptozotocin-induced diabetes mellitus. However, further investigations are recommended for establishing fenugreek as a safe, useful effective agent to minimize the increment in amount of connective tissue in thymic section improving the diabetic condition by acting as antidiabetogenic agent. Key words: Diabetes mellitus; Connective tissue; Fenugreek; Thymus DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8149 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 49-52